Between “Here” and “There”: Toward Understanding Emigration Representations and Perceptions Among Algerian Physicians - Benfifi, Taqiyeddine (Italian Sociological Review, 2025)
The present study explores the motives and perceptions of emigration among physicians working at the University Center Hospital Benflis Al-Tohamy Batna-Algeria. It aims at exploring their representations and views from an Algerian socio-cultural perspective. Data were collected in-situ to grasp the essence of the phenomenon and the conditions under which physicians work and develop their intention to relocate. Purposive and snowballing sampling were chosen to apply the unstructured interview for data collection. Content analysis was used to extract the main themes related to physicians’ experiences. The findings reveal that physicians experience a range array of internal and external conditions that feed their desire to move abroad. The main themes related to emigration motivation and perceptions were: working conditions, quality of life, socio-economic incentives, and cultural motives. The study shows that post-migration perceptions of doctors reflect the influence of former emigrants’ narratives on non-emigrants, with living conditions being compared “here” and “there”, which interestingly nourish migration intentions. The motives that drive the inflow of medical doctors from Algeria should be considered by both policy makers and researcher to develop our understanding and mitigate its deleterious effects.